AHR/ROS-mediated mitochondria apoptosis contributes to benzo[a]pyrene-induced heart defects and the protective effects of resveratrol. (October 2021) - Huang, Yujie; Zhang, Jie; Tao, Yizhou; Ji, Cheng; Aniagu, Stanley; Jiang, Yan; Chen, Tao
Graphical abstract: Highlights: BaP-induced heart defects in zebrafish embryos were attenuated by either CH or NAC. BaP induces oxidative stress via AHR activation, leading to intrinsic apoptosis. Both CH and NAC antagonized BaP-induced oxidative stress and intrinsic apoptosis. RSV protected against BaP-induced heart defects by inhibiting ROS production. Abstract: Benzo[a]pyrene (BaP), a prototypical polycyclic aromatic hydrocarbon, is widely present in the environment. BaP-induced heart defects have been frequently reported, but the underlying molecular mechanisms remain elusive. Here, we found that BaP increased heart malformations in zebrafish embryos in a concentration-dependent manner, which were attenuated by supplementation with either CH223191 (CH), an aryl hydrocarbon receptor (AHR) inhibitor, or N-acetyl-l -cysteine (NAC), a reactive oxygen species (ROS) scavenger. While CH and NAC both inhibited BaP-induced ROS generation, NAC had no effect on BaP-induced AHR activation. We further demonstrated that BaP increased mitochondrial ROS, decreased mitochondrial membrane potential, and caused endogenous apoptosis, with all these effects being counteracted by supplementation with either CH or NAC. Resveratrol (RSV), a natural AHR antagonist and ROS scavenger, also counteracted the heart malformations caused by BaP. Further experiments showed that RSV attenuated BaP-induced oxidative stress, mitochondrial damage and apoptosis, but had no significant effect on AHR activation. In conclusion, our findings show that BaP induces oxidative stress via AHR activation, which causes mitochondria-mediated intrinsic apoptosis, resulting in heart malformations in zebrafish embryos, and that RSV had a protective effect against BaP-induced heart defects mainly by inhibiting oxidative stress rather than through antagonism of AHR activity.